High sensitive depleted MOSFET-based neutron dosimetry - Fragopoulou, M.; Konstantakos, V.; Zamani, M.; Siskos, S.; Laopoulos, T.; Sarrabayrouse, G. (HNPS Advances in Nuclear Physics, 2019)
A new dosemeter based on a depleted Metal-Oxide-Semiconductor field effect transistor, sensitive to both neutrons and gamma radiation was manufactured at LAAS-CNRS Laboratory, Toulouse France. In order to be used for neutron dosimetry a thin film of lithium fluoride was deposited on the surface of the gate of the device. The characteristics of the dosemeter such as its response to neutron dose were investigated. The response in thermal neutrons was found to be high. In fast neutrons the response was lower than that of thermal neutrons but higher than the one presented in literature.